Development of an effective PR strategy for International Turkic Culture and Heritage Foundation - Asadov, Ruslan; Osmanli, Aysel; Suleimenova, Ainara (ADA University, 2023)
This capstone project analyzes the ways of strengthening a PR strategy of a young international organization namely the International Turkic Culture and Heritage Foundation (ITCHF), which operates under the umbrella of a wider international institution such as the Organization of Turkic States (OTS). The research revealed 3 challenges, which prevent the development of ITCHF’s PR strategy − lack of visibility on social media, a limited number of observer-states, and insufficient cooperation with non-Turkic international organizations. Further, the study proposes 3 policy options, which are aimed at overcoming these challenges, namely, changing the strategy of maintaining social media accounts, expansion of the number of observer-states, and increasing cooperation with other international organizations. All these policy alternatives were evaluated according to 5 main criteria such as effectiveness, efficiency, equity, feasibility, and flexibility. The analysis identified that the most relevant policy options, which can be implemented in order to enhance the PR strategy of ITCHF and increase its visibility in the international arena are associated with reconsidering the strategy of social media maintenance and enlargement of cooperation with other international organizations.
Keywords: Public relations -- International organizations; Cultural organizations -- Management; Social media -- Strategic use; Public and International Affairs